Integrated genomics, metagenomics and metatranscriptomics to reveal the biocontrol mechanism of Bacillus velezensis JY10 against tobacco target spot disease - Yang, Wenjuan; Liu, Hui; Xu, Rubing; Peng, Yiqian; Xu, Tingting; Yang, Yong; Li, Yanyan; Xiang, Haibo (Frontiers in Microbiology, 2025)
Tobacco target spot (TTS) disease, a prevalent fungal disease caused by Rhizoctonia solani, severely reduces tobacco yield and quality, imposing substantial economic losses on the tobacco industry. In this study, we employed a biological control approach against TTS using a Bacillus velezensis JY10 isolated from healthy tobacco stems. We further elucidated the mechanism of JY10 in controlling TTS through genomics, metagenomics and metatranscriptomics. The results showed that JY10 exhibited robust inhibitory effects against R. solani, with an inhibition rate exceeding 95%, and achieved a TTS control efficacy of 68.63% in pot experiments. Whole-genome sequencing demonstrated that the JY10 genome spans 3,929,772 bp, contains 4,026 protein-coding genes, and has a GC content of 46.5%. AntiSMASH analysis predicted 12 secondary metabolite biosynthetic gene clusters, encoding antimicrobial compounds such as surfactin, fengycin, difficidin, bacillaene, bacillibactin, macrolactin H, and bacilysin. Metagenomic profiling showed that JY10 treatment had no significant influence on tobacco phyllosphere and rhizosphere microbiome structure, however, it significantly increased the relative abundance of beneficial microbes, including Bacillus, Pseudonocardia, and Pseudomonas. Metatranscriptomic analysis revealed that JY10 might enhance tobacco TTS resistance by modulating oxidative phosphorylation pathway and upregulating several antibiotics biosynthesis. Taken together, JY10 may employ a dual control strategy against TTS, involving the direct production of antifungal compounds, as well as indirectly increasing the abundance of beneficial microbes and modulating their oxidative phosphorylation and antibiotic synthesis pathways in the phyllosphere and rhizosphere of tobacco. These findings provide a theoretical foundation for understanding biocontrol mechanisms of JY10 and introduce a promising bacterial resource for the development of sustainable TTS management strategies.